2018
DOI: 10.1002/glia.23301
|View full text |Cite
|
Sign up to set email alerts
|

A single‐cell analysis reveals multiple roles of oligodendroglial lineage cells during post‐ischemic regeneration

Abstract: NG2 cells represent precursors of oligodendrocytes under physiological conditions; however, following cerebral ischemia they play an important role in glial scar formation. Here, we compared the expression profiles of oligodendroglial lineage cells, after focal cerebral ischemia (FCI) and in Alzheimer's-like pathology using transgenic mice, which enables genetic fate-mapping of Cspg4-positive NG2 cells and their progeny, based on the expression of red fluorescent protein tdTomato. tdTomato-positive cells posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 61 publications
7
28
0
Order By: Relevance
“…To further increase the complexity of this scenario, consistent with previous findings [207,208], in vivo two-photon imaging analyses revealed an assortment of distinct NG2 glia reactions to injury, with some cells starting migration toward the lesion site, others entering cell cycle, and others displaying only hypertrophy and morphological changes [31,86]. Single-cell messenger-RNA (mRNA) profiling of NG2 glia after focal cerebral ischemia also identified at least three subpopulations of cells that could be distinguished according to changes in their expression patterns [19]. Such behavioral and molecular heterogeneity suggests the existence of diverse NG2 glia subsets which respond differently to CNS injury.…”
Section: Ng2 Glia Upon Central Nervous System Injury and Stresssupporting
confidence: 90%
See 2 more Smart Citations
“…To further increase the complexity of this scenario, consistent with previous findings [207,208], in vivo two-photon imaging analyses revealed an assortment of distinct NG2 glia reactions to injury, with some cells starting migration toward the lesion site, others entering cell cycle, and others displaying only hypertrophy and morphological changes [31,86]. Single-cell messenger-RNA (mRNA) profiling of NG2 glia after focal cerebral ischemia also identified at least three subpopulations of cells that could be distinguished according to changes in their expression patterns [19]. Such behavioral and molecular heterogeneity suggests the existence of diverse NG2 glia subsets which respond differently to CNS injury.…”
Section: Ng2 Glia Upon Central Nervous System Injury and Stresssupporting
confidence: 90%
“…In line with this view, a subpopulation of NG2 glia has been observed to serve as multipotent progenitors, producing protoplasmic astrocytes as well OLs in the embryonic ventral forebrain or following some kinds of CNS injury [19,[24][25][26][27]. It has also been proposed that adult NG2 glia may activate spontaneous neurogenic events within restricted brain areas [28].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…While we describe the transcriptional profile of OPCs during homeostasis, it is important to note that understanding the role of OPCs in the healthy brain will provide a necessary foundation for examining any protective or detrimental novel functions in desease pathology. Previous work has demonstrated that OPCs exhibit significant transcriptional heterogeneity and disease-associated signatures in models of multiple sclerosis and cerebral ischemia, and showed significant transcriptional changes in human Alzheimer's disease patients 18,59,76 .…”
Section: Discussionmentioning
confidence: 99%
“…This morphology is characterized by thickened and highly ramified processes, as opposed to the relatively thin and unbranched prolongations of non-reactive NG2-glia [17]. Furthermore, NG2-glia display both molecular and behavioral heterogeneity following brain injury [17,21,22], producing both beneficial and deleterious effects [8,21,[23][24][25][26][27]. However, little is known about the existence of certain subsets of NG2-glia that produce a specific response to brain damage and whether their fate may already be determined early in embryonic development.…”
Section: Introductionmentioning
confidence: 99%